MATERNAL OBESITY AS A PREDICTIVE MARKER FOR ADVERSE PREGNANCY OUTCOME: A CASE–CONTROL STUDY - JYOTI SAINI; SAWAI SINGH LORA; MONICA CHETANI GUPTA (Asian Journal of Pharmaceutical and Clinical Research, 2023)
Objective: Obesity in pregnancy is an important risk factor for adverse maternal and neonatal outcomes. In the past, various studies have compared adverse pregnancy-related outcomes between obese and normal body mass index (BMI) mothers. In the present study, we aimed to examine the impact of obesity class on maternal and perinatal outcomes. The aim of the study was to evaluate the association between maternal adiposity and pregnancy outcomes. Methods: A prospective and cross-sectional study conducted at Zanana Hospital SMS Medical College Jaipur on 68 antenatal obese/overweight woman (BMI>25 kg/m2) and 68 control antenatal woman (BMI<25 kg/m2) with singleton pregnancies. Results: The incidence of gestational diabetes was 8.82% and 2.94%, respectively, in obese and control group. The incidence of pre-eclampsia was 14.70% and 5.88% in obese and control group. The incidence of gestational hypertension was 8.82% and 5.88% in obese and control group. The cesarean delivery rates were higher in obese group (55.88%) than control group (32.35%). About 20.58% of babies born to obese women and 8.82% of babies born to control were admitted in NICU (p<0.05). The incidence of pre-term delivery, fetal abnormality, and macrosomia was higher in obese group as compared to control group. Conclusions: Obesity increases the risk of many adverse maternal and neonatal outcomes. Therefore, appropriate measures must be taken to reduce obesity incidence in women of reproductive age to circumvent the adverse maternal and neonatal outcomes associated with obesity.